A CASE OF ACUTE LYMPHOBLASTIC LEUKEMIA PRESENTING WITH HYPEREOSINOPHILIA - Bengü Macit; Arzu Akyay; Yurday Öncül (Hematology, Transfusion and Cell Therapy)
Case Report: Hypereosinophilia (HE) is eosinophil count >500/μL. The association of HE with acute lymphoblastic leukemia (ALL) is extremely rare, with an incidence of less than 1%. HE may precede the common symptoms and signs of ALL by several months or weeks. In some cases, the symptoms may be due to eosinophilic organ or system infiltration, and these findings may be different from the classical ALL symptoms, thus delaying the diagnosis. Here, we report a male patient who presented with HE and was diagnosed as PreB-ALL.A 9-year-old boy patient was admitted to Inonu University Turgut Özal Medical Center with complaints of testicular pain and swelling. The patient's hemogram showed HE, but there was no leukocytosis or cytopenia.. No atypical cell was observed in peripheral smear. On scrotal ultrasonography (USG), the left epididymal head had a mildly heterogeneous appearance and the patient was treated for epididymitis with suspicion of epididymitis. Approximately one week later, the patient presented with fever . The patient's peripheral smear showed 36% blasts, 38% eosinophils, 2% monocytes, 6% lymphocytes, 10% segments and 8% bands. Bone marrow aspiration was performed for the diagnosis of acute leukemia and PreB-ALL was diagnosed. Control testicular USG was evaluated as testicular involvement of leukemia. During follow-up, the patient had nausea, vomiting, dizziness, decreased visual field, nuchal rigidity, and outward gaze limitation. Magnetic resonance (MR) venography revealed thrombosis in the inferior sagittal sinus and anticoagulant therapy was initiated. The patient with central nervous system symptoms was considered to have leukemic involvement and his treatment was adjusted.ALL is a condition that can cause HE. The prognosis is poor in ALL patients presenting with HE. HE may occur before the classical ALL symptoms therefore the diagnosis of ALL should also be considered in patients presenting with HE.